The Effect of Subsidy Reform Program on Food Security in Iran - Seyyed Safdar Hosseini; Mohammad Reza Pakravan Charvadeh; Habibollah Salami (فصلنامه پژوهش‌های اقتصادی ایران, 2016)
One of the main approaches to achieve food security is redistribution measures such as the subsidy reform program with the aim of social justice and improved welfare of low-income groups. In this study, we analyzed the effect of the implementation of targeted subsidies program on food security in Iran during 2005-2012. A model of food security was estimated after calculating the adult’s energy intake through household’s consumption information. We found an inverse relationship between the subsidy reform program and food security among Iranian households. Due to this program, food prices increased and households’ real income decreased. The results of these changes are the increased cost of living and decreased share of income spent on food.